Pendidikan Karakter dalam Anime: Analisis Psikologi Tokoh Naruto pada Serial Anime Naruto - Illa, Hafitta; Surur, Misbahus (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 6 No 1 (2024), 2024)
Naruto anime is one of the anime that can be used as an educational watch that supports us in teaching character education to the younger generation. The purpose of this study is to analyze the psychology of the main characters of Naruto anime and find out the influence of Naruto anime in shaping characters and values in the audience. This study used a qualitative approach with data collection techniques, watch-listen-record and read-record. From this research, it can be found that there are several psychological aspects of Naruto characters, namely 1) loneliness and rejection, 2) social care, 3) motivation and determination, 4) self-development, 5) courage and confidence, 6) empathy, and the influence of the anime in shaping the character and values in the audience, namely 1) inspiration to overcome obstacles, 2) the importance of friendship, 3) face conflict peacefully, 4) courage to oppose injustice. The conclusion obtained is that the character Naruto shows a rich journey in terms of psychology, from a difficult childhood to strong self-development. In addition, Naruto Anime can inspire and shape characters and values in its audience.